Neurodegenerative diseases : pathology, mechanisms, and potential therapeutic targets - Beart, P. M.; Robinson, Michael; Rattray, Marcus; Maragakis, Nicholas J. (Advances in neurobiology, 2017)
Provides a timely overview of critical advances in molecular and cellular neurobiology, covers key methodologies driving progress, and highlights key future directions for research on neuronal injury and neurodegeneration relevant to neuronal brain pathologies. The editors bring together contributions from internationally recognized workers in the field to provide an up to date account of how and why molecular and cellular neurobiology is such an important area for clinical neuroscience. Understanding the molecular aspects of a number of neurodegenerative conditions such as Parkinson's or Alzheimer's disease for the purpose of improving patient management remains a major challenge of neurobiology be it from the basic or clinical perspective. A strategic evaluation of research contributions and the power of modern methods will help advance knowledge over the next years.